2016
DOI: 10.4103/0975-7406.171699
|View full text |Cite
|
Sign up to set email alerts
|

Statins and its hepatic effects: Newer data, implications, and changing recommendations

Abstract: Hepatic adverse effects are one of the most commonly known adverse effects reported with statins. Frequently, fear of serious hepatic effects contributes to underutilization of statins as well as unnecessary discontinuation of its use among those indicated. There are changing data on the occurrence of these negative hepatic effects, recommendations on their actual risk, monitoring required, and safety of use in those with preexisting hepatic disorders. Based on reviewed literature, statins appear to be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 76 publications
3
45
0
2
Order By: Relevance
“…Elevation of liver enzymes is observed in a small proportion of patients taking statins (3%), and an even smaller part of these patients progress to hepatitis (Jose, 2016;Russo et al, 2014). In this study, the frequency of liver enzymes elevation (2.5%) was similar to that of these previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Elevation of liver enzymes is observed in a small proportion of patients taking statins (3%), and an even smaller part of these patients progress to hepatitis (Jose, 2016;Russo et al, 2014). In this study, the frequency of liver enzymes elevation (2.5%) was similar to that of these previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The liver damage mechanisms are not fully understood. It is known that the lesion may have hepatocellular, cholestatic or autoimmune patterns (Jose, 2016;Mancini et al, 2013;Russo et al, 2014). The most common histopathological findings in statin hepatotoxicity is portal inflammation with lymphocytes, with or without cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…Schooling et al have previously suggested that lower levels of androgens might cause higher risk of diabetes via lower muscle mass 46 and poor liver function may reduce androgens, 47 consistent with the sex differences observed. Additionally, it is also consistent with statins usage which is associated with lower testosterone, 51 elevated aminotransferase levels, 52 and higher diabetes risk. 53 Etiologically, these findings are consistent with the evolutionary public health, i.e., growth and reproduction trading-off against longevity, which may inform the identification of interventions.…”
Section: Discussionsupporting
confidence: 68%
“…For reasons of comparison, the regularly used maximum dose for reducing cholesterol levels in humans is about ≈1.14 mg/kg/d for a 70 kg person. Local application instead of systemic administration is also supported by the following facts: (i) 10%‐25% of patients taking statins systemically report muscle symptoms, are exposed to an increased risk for myopathy and hepatotoxicity and also present a slightly higher risk for developing diabetes mellitus; (ii) these side effects are dose‐dependent; (iii) neither herein nor in clinical studies have any remarkable adverse reactions been reported after local statin application, except for some local postoperative inflammation; and (iv) no systemic effects of local application have been detected (e.g., no alterations in the nearby submandibular lymph nodes, liver enzyme levels, numbers of white blood cells and immune cells and body weight). Nevertheless, it must be mentioned that local application of high statin concentrations may also exert an antiproliferative and even an apoptotic effect on periodontal cell types (i.e., gingival fibroblasts, periodontal ligament stem cells); therefore, there is space for optimization of dose and delivery systems.…”
Section: Discussionmentioning
confidence: 99%